Technological and economic design of asphalt mixture composition based on optimization methods - Sivilevičius, Henrikas; Vislavičius, Kęstutis; Bražiūnas, Justas (Technological and Economic Development of Economy, 2017)
The asphalt pavement made of high quality materials and having the optimal composition best resists destructive effects of environmental factors and vehicles. The optimal content of the mineral materials of the asphalt mixture and a bituminous binder is selected employing calculation and experimental methods. The properties of the designed asphalt mixture must meet the requirements of technical specifications thus reducing its cost. The paper presents algorithms for simulating the composition of the asphalt mixture applying mathematical programming techniques. The algorithms allow designing the asphalt mixture with minimal bitumen content, a low cost of the mineral part and the densest gradation assessing technological requirements for producing the mixture. Optimal bitumen content is calculated considering bitumen capacities specified for different types of rock and determined employing the most recent standard sieves screening for narrow fractions. For verifying the new proposed algorithms, a numerical experiment on the materials most commonly used in asphalt mixing plants was done. The analysis of findings indicates that the application of the algorithms assist in comparing real results. First published online: 03 Apr 2017